Effectiveness of fixed-dose combination of rosuvastatin and ezetimibe in heterozygous familial hypercholesterolemia from the RENAISSANCE registry - I. A. Alekseeva; U. V. Chubykina; M. V. Ezhov; A. V. Tyurina; T. E. Kolmakova; N. A. Tmoyan; A. A. Sokolov; T. A. Rozhkova; N. S. Kurochkina; I. V. Sergienko; I. V. Avdeeva; V. E. Oleynikov; et al. (Рациональная фармакотерапия в кардиологии)
Aim. To study the adequacy and effectiveness of lipid-lowering therapy (LLT) prescribed to patients with heterozygous familial hypercholesterolemia (HeFH), including fixed-dose combinations (FDC) of rosuvastatin with ezetimibe, as well as the frequency of achieving target low-density lipoprotein cholesterol (LDL-C) levels.Material and methods. The clinical and demographic data of 3151 patients with HeFH at high or very high cardiovascular risk from the RENAISSANCE registry were retrospectively analysed. Among the 1612 individuals receiving LLT, 477 patients were treated with a combination of rosuvastatin at various doses and ezetimibe 10 mg daily, either as a free combination or as a FDC.Results. The median age of the patients was 46.0 [32.0; 57.0] years. The median LDL-C level was 6.4 [5.3; 7.8] mmol/L. Although LLT was recommended to all participants, approximately half (49%, n=1539) were not receiving treatment. Among the 1612 patients on LLT, 44% (n=703) received statin monotherapy, and 43% (n=697) were treated with a combination of statins and ezetimibe. Of the 477 patients taking rosuvastatin with ezetimibe, the majority were active adults of working age (35-64 years): 335 (80%) vs 86 (20%), p <0.05. Most patients preferred taking rosuvastatin with ezetimibe in the FDC: 357 (74.8%) vs 120 (25.2%), p <0.05. Among those on FDC, a significantly higher proportion used Zenon® compared to other FDCs: 44.4% (n=212) vs 30.4% (n=145), p <0.05. A significant reduction in LDL-C was observed compared to baseline: 61% in the free combination group and 65% in the FDC group, including a 67% reduction in the Zenon® subgroup (p <0.001). The rate of achieving LDL-C targets among high/very high cardiovascular risk patients was lower in the free combination group compared to the FDC group, with the highest rates observed among Zenon® users: 5.8% (n=7), 17.9% (n=26), and 21.7% (n=46), respectively (p <0.01).Conclusion. Among patients with НeFH, the use of a FDC of rosuvastatin and ezetimibe is associated with higher treatment adherence and a greater likelihood of achieving target LDL-С levels.